Camillo Sitte - Gesamtausgabe. Schriften und Projekte Band 1: Schriften zu Kunstkritik und Kunstgewerbe - Sitte, Camillo (2007)
In the Project P16901-G06 sponsored by the FWF, Camillo Sittes writings will be published for the first time in a "critical comprehensive edition", scheduled for six volumes. The basis for this edition is provided by the "Sitte Nachlass-Archiv" which is owned by the Technical University, Vienna. The writings of volume one consist of Sittes publications in the field of art criticism and the applied arts. Those writings have been, in most cases, shorter publications in newspapers and journals which are difficult to access today. The unpublished and undated autograph "Faust, Fliegender Holländer und Meistersinger" as well as one letter to Richard Wagner from 1873, which is not contained in the Sitte archive, supplement his writings in the field of art criticism. The writings in the field of applied arts throw a new light onto the work of Camillo Sitte as director of vocational schools (i.e. Kunstgewerbeschulen), who elsewise is predominantly known as urban theorist and urban planner only. Those wrintigs give testimony to the political ambitions to foster the applied arts in the k. u. k. monarchy around Rudolf Eitelberger von Edelberg. They comprise almost all areas of arts and craft, ranging from traditional and local trades to the beginnings of industrial production. The writings in the field of art criticism derive mainly from Sittes early time in Vienna and document the vivid debates on the question of art between historism and emerging modern currents like secession, impressionism and expressionism. Furthermore, this thematic field contains a series of writings on Richard Wagner's conception of art which illustrate Sittes own apprehension of art, as it will have impact especially on his chief work, "City Planning According to Its Artistic Principles" from 1889 (vol. 3 of this edition). Michael Mönninger and Wolfgang Sonne / Ruth Hanisch put these texts into context, inform about the current state of research and establish connections to others of Camillo Sitte's fields of activity, which will be documented in the volumes of this edition to come. Furthermore, there is an extensive essay on the biography of Camillo Sitte by Michael Mönninger. Editorial work is done by Sonja Hnilica and Bernhard Langer. The Editors are Klaus Semsroth, Michael Mönninger and Christiane C. Collins.